Increase in Motorized Vehicle Tax (PKB) Revenue Through Tax Clearing at the Dompu Samsat Joint Office - Anna Pratiwi (Journal AGENCY, 2022)
This study aims to test and determine the increase in tax revenue before and after it is applied to the SAMSAT Dompu Joint office. This research is quantitative descriptive. This is obtained through interviews and documentation. Data analysis was performed by comparing the amount of motor vehicle tax revenue before and after the tax return. The results of the research show that: Tax revenue after the implementation of the Kring Tax is proven to be able to tie motor vehicle tax receipts with the numbers recorded in the SAMSAT Dompu Office report which is IDR 6,734,770,347, while in 2016 it was IDR 9,205,731,543 and continues to increase until 2018. which is IDR 10,729,544,167, of which the biggest contribution to motor vehicle tax collection is the type of motorbike with a total of IDR 4,206,763,159 in 2018 and IDR 4,349,173,575 in 2019. Constraints faced during motor vehicle tax collection are: lots of data taxpayers who are not in accordance with the BPKB, not to mention taxpayers who have transferred ownership but do not report.